Public art's "right to the city": determining various role players' perceptions, experiences and preferences for public art in public spaces in the City of Cape Town. - Walters, Clyde Ross (Stellenbosch : Stellenbosch University, 2017)
Thesis (MA)--Stellenbosch University, 2017.